Greed, Opportunity Pemicu Fraud Dengan Moderasi Idealisme Pimpinan - Sulistianingsih (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2023)
This study aims to examine the effect of greed, opportunity on fraud Procurement of Government Goods / Services with moderated leadership ideals. This type of research is quantitative research, using a questionnaire as a research instrument. The method of analysis in this study used the Partial Least Squares Structural Equation Modeling (PLS SEM) . The results showed that greed, opportunity has positive effect on fraud Procurement of Government Goods / Services. These results show that the higher the greed in individuals, the higher the potential to commit fraudulent acts of procurement of goods/services. The higher the opportunity to commit fraud, the higher the potential for someone to commit fraud. Moderate variable analysis shows that the idealism of the leader is able to moderate the greed and opportunity.